Acute Encephalitis Associated with SARS-CoV-2 Confirmed in Cerebrospinal Fluid: First Case in Malaysia - Tee, Tze Yuan; Alif Adlan, Mohd Thabit; Khoo, Ching Soong; Hisham, Md Shahrom; Chan, En Ze; Marsilla Mariaty, Marzukie; Zul Amali, Che Kamaruddin; Ravindran, Thayan; Suresh Kumar, Chidambaram (Korean Neurological Association, 2021)
A 69-year-old male with hypertension and atrial fibrillation presented with a 4-day history of fever, cough, and breathlessness, and subsequently developed disorientation and confusion for 1 day. On arrival, his Glasgow Coma Scale was 12/15 (E4, V3, and M5). His body temperature was 37.5°C, blood pressure was 136/60 mm Hg, pulse rate was 72 beats/min , and SpO2 was 98%, with a nasal prong of 3 L/min. There were no symptoms of meningism or longtract signs. On the following day he became increasingly restless and breathless, and required a high-flow-rate nasal cannula to maintain adequate oxygenation. A diagnosis of Coronavirus disease-2019 (COVID-19) was established based on positivity when using an antigen rapid testing kit (SD Biosensor, Inc., Suwon, Korea). However, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was not detected when the polymerase chain reaction (PCR) was applied to the nasopharyngeal swab sample. High-resolution CT of his lungs showed subpleural ground-glass opacities with reticulation on the background of chronic lung changes. Noncontrast brain CT only revealed an old right lenticular infarct. The opening pressure in lumbar puncture was 9.5 cmH2O. His cerebrospinal fluid (CSF) was clear, with a protein level of 1.16 g/L, and the CSF/serum glucose ratio was 0.58. A white blood cell count of 50 cells/mm3 with 100% lymphocytes was seen in the CSF. SARS-CoV-2 was detected in his CSF using PCR with a cycle threshold value of 36.08 and the ORF1ab gene. The results of other CSF analyses were unremarkable.